Unraveling Mass Transfer and Reaction Processes in CVD-Grown MoS2 Films: A Multiphysical Field Coupling Study - Zhen Yang; Jinwei Lin; Qing Zhang; Yutian Liu; Shujun Han; Yanbin Zhou; Shuo Chen; Shenlong Zhong; Xianli Su; Qingjie Zhang; Xinfeng Tang (Applied Sciences)
The two-dimensional semiconductor material MoS2, grown via chemical vapor deposition, has shown significant potential to surpass silicon in advanced electronic technologies. However, the mass transfer and chemical reaction processes critical to the nucleation and growth of MoS2 grains remain poorly understood. In this study, we conducted an in-depth investigation into the mass transfer and chemical reaction processes during the chemical vapor deposition of MoS2, employing a novel multi-physics coupling model that integrates flow fields, temperature fields, mass transfer, and chemical reactions. Our findings reveal that the intermediate product Mo3O9S4 not only fails to participate directly in MoS2 film growth but also hinders the diffusion of MoS6, limiting the growth process. We demonstrate that increasing the growth temperature accelerates the diffusion rate of MoS6, mitigates the adverse effects of Mo3O9S4, and promotes the layered growth of MoS2 films. Additionally, lowering the growth pressure enhances the convective diffusion of reactants, accelerating grain growth. This research significantly advances our understanding of the mass transport and reaction processes in MoS2 film growth and provides critical insights for optimizing chemical vapor deposition systems.